(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides brief information about the scientific activity of Tilman Nagelnin, a German Islamic scholar who conducted scientific research on Amir Timur and the Timurids. Also, Tilman Nagel’s views on the personality of Amir Temur and his state activities are analyzed. In addition, Amir Temur’s thoughts about the struggle for the throne after his death are also analyzed.